Modelling of impact on a fuel tank using smoothed particle hydrodynamics - Vignjevic, Rade; De Vuyst, Tom; Campbell, James C.; Bourne, Neil K. (Cranfield University, 2005)
This paper describes a modelling approach for the simulation of hypervelocity impact on fuel tanks using the Smoothed Particle Hydrodynamics (SPH) method. To determine a suitable particle density, three two-dimensional axi-symmetric models were analysed. Then three-dimensional simulations with cylindrical and cubic penetrators were performed. For each analysis the transient pressure values at locations corresponding to experimental transducer locations were recorded. The pressure time histories are shown for the axi-symmetric and 3D models. The simulation results are compared with the experimental results. The purpose of the research was to demonstrate the capability and potential of SPH for simulating this type of problem.